The Impact of the TikTok Ban on the Political Relations between the United States and China - Haris, Umiyati; Saputro, Eko Rachmat; Adam, Aenal Fuad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The ban on TikTok in the United States has been one of the most controversial policies that have had a major impact on US-Tiongkok bilateral relations. This policy is based on national security reasons, but it also reflects the dynamics of geopolitical competition between the two countries. Using Gilpin's Realism approach, this study analyses how the TikTok ban reflects the US' efforts to maintain its dominance in the global economy and technology. Applying content analysis and data triangulation methods, this study collected information from various sources, including government policies, trade reports, and international media coverage. The results show that this policy exacerbated tensions between the US and Tiongkok, especially in the trade sector and technology industry. In response, Tiongkok imposed retaliatory policies by increasing trade tariffs on US products and restricting American technology companies' access to its domestic market. In addition, the data shows that although the total value of trade between the two countries is still in the trillions of dollars, the escalating tensions may hinder growth and encourage diversification of global supply chains. The findings confirm that the hegemonic competition between the US and Tiongkok is not only in the economic sphere, but also in the aspects of technology regulation and cybersecurity. This research provides insights into the impact of the TikTok ban on the US-Tiongkok relationship, as well as how the strategic steps of the two countries in facing the changing global economic and political landscape.